2021
DOI: 10.3390/ijerph18178935
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Assessed in Children with Adenoid Hypertrophy

Abstract: Introduction: The quality of life issue began to be earnestly studied in the second half of the 20th century. It had originally been used as a criterion for measuring levels of human development in the USA and Western Europe. At first, only objective parameters were assessed, such as material goods; however, later, subjective and non-material parameters were added, such as health, freedom, and happiness. Over time, more and more attention has been paid to the subjective parameters regarding any quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…The PedsQL, is a generic measure that addresses health profiles across four domains and is not specifically tailored to stressful events such as the COVID-19 pandemic. It has been noted before that specific HRQoL instruments (e.g., with elements appropriate to this particular situation) are more sensitive in detecting deviations occurring over time [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PedsQL, is a generic measure that addresses health profiles across four domains and is not specifically tailored to stressful events such as the COVID-19 pandemic. It has been noted before that specific HRQoL instruments (e.g., with elements appropriate to this particular situation) are more sensitive in detecting deviations occurring over time [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life (QoL) is an essential outcome measure for both general and mental health. The research literature recognizes the vital importance of QoL measures in addressing adolescents’ health [ 3 , 4 , 5 ]. Stressful events such as war or pandemics can cause QoL disruptions.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a condition-specific QOL questionnaire for children with EA could contribute to a better understanding of the patient's life situation, provide healthcare facilities with a more accurate and reliable tool for patient evaluation and in the long-term help improve patient care. Together with a generic QOL questionnaire, such a questionnaire is likely to allow for a comprehensive assessment of the patient's condition [16][17][18]. In recent years, a set of age-specific condition-specific QOL questionnaires for children and adolescents with EA were developed and these have shown sound psychometric performance in Sweden, Germany and Turkey [3,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This investigation demonstrated that no major variations existed across social activity, pain, discomfort, or family cohesion [11]. Peak reductions in well-being were identified within AH cases, mainly affecting behavior, general health concepts, and mental health [11].…”
Section: Association Of Ome and Ahmentioning
confidence: 75%
“…In a separate study shortlisted in this review, children (eight to 12 years of age; 54 girls; 47 boys; mean age was 8.62 years) compiled the Child Health Questionnaire-Parent Form 50 (CHQ-PF50) [11]. This investigation demonstrated that no major variations existed across social activity, pain, discomfort, or family cohesion [11]. Peak reductions in well-being were identified within AH cases, mainly affecting behavior, general health concepts, and mental health [11].…”
Section: Association Of Ome and Ahmentioning
confidence: 99%